2021
DOI: 10.1039/d1ra07952b
|View full text |Cite
|
Sign up to set email alerts
|

Electroless deposition of Ni–P/Au coating on Cu substrate with improved corrosion resistance from Au(iii)–DMH based cyanide-free plating bath using hypophosphite as a reducing agent

Abstract: In the Au(iii)–DMH based cyanide-free electroless gold plating bath, the added hypophosphite inhibited the black pad and improved the corrosion resistance of the Cu/Ni–P/Au coating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…For the reduction of resistance, gold plating on the electrolyzer surface can be attempted. 48 For the problem of carbonate precipitation blocking the active site, this is a difficulty common to MEA-type electrolytic cells at present. We will summarize a detailed solution in the subsequent part of the perspective.…”
Section: Large-area Co 2 Rr Electrolyzermentioning
confidence: 99%
“…For the reduction of resistance, gold plating on the electrolyzer surface can be attempted. 48 For the problem of carbonate precipitation blocking the active site, this is a difficulty common to MEA-type electrolytic cells at present. We will summarize a detailed solution in the subsequent part of the perspective.…”
Section: Large-area Co 2 Rr Electrolyzermentioning
confidence: 99%
“…5(b). The bright green isosurface between the NB molecule and 5-HCIA 2À ligand reveals the van der Waals force 49,50 and indicates the presence of p-p interactions between NB and Cd-HCIA-1. The binding energy of the NB@Cd-HCIA-1 complex was 2.99 eV, which indicated that the formation of the complex was thermodynamically feasible.…”
Section: Host-guest Interaction Between Nitrobenzene and Cd-hcia-1mentioning
confidence: 99%